Survival benefit of levetiracetam in patients treated with concomitant chemoradiotherapy and adjuvant chemotherapy with temozolomide for glioblastoma multiforme. Issue 17 (14th May 2015) - Kim, Young‐Hoon; Kim, Tackeun; Joo, Jin‐Deok; Han, Jung Ho; Kim, Yu Jung; Kim, In Ah; Yun, Chang‐Ho; Kim, Chae‐Yong
Abstract : BACKGROUND: A chemosensitizing effect of levetiracetam (LEV) has been suggested because LEV inhibits O‐6 methylguanine‐DNA methyltransferase (MGMT). However, the survival benefit of LEV has not been clinically documented. The objective of this study was to assess the survival benefit of LEV compared with other antiepileptic drugs as a chemosensitizer to temozolomide for patients with glioblastoma. METHODS: In total, 103 consecutive patients with primary glioblastoma who received concomitant chemoradiotherapy and adjuvant chemotherapy with temozolomide were retrospectively reviewed, and 58 patients (56%) received LEV during temozolomide chemotherapy for at least 3 months. A Cox regression survival analysis was performed to adjust for confounding factors, including age, extent of lesion, Karnofsky performance scale score, extent of removal, and MGMT promoter methylation status. RESULTS: The median progression‐free survival (PFS) and overall survival (OS) for patients who received LEV in combination with temozolomide (PFS: median, 9.4 months; 95% confidence interval [CI], 7.5‐11.3 months; OS: median, 25.7 months; 95% CI, 21.7‐29.7 months) were significantly longer than those for patients who did not receive LEV (PFS: median, 6.7 months; 95% CI, 5.8‐7.6 months; OS: median, 16.7 months; 95% CI, 12.1‐21.3 months; P  = .010 and P  = .027, respectively). In multivariate analysis, the variables that were identified as significant prognostic factors for OS were preoperative Karnofsky performance scale score (hazard ratio [HR], 0.37; P  = .016), MGMT promoter methylation (HR, 0.30; P  = .002), and receipt of LEV (HR, 0.31; P  < .001. CONCLUSIONS: LEV may provide a survival benefit in patients with glioblastoma who receive temozolomide‐based chemotherapy. A prospective randomized study may be indicated. Cancer 2015;121:2926–2932. © 2015 American Cancer Society . Abstract : Levetiracetam may provide a survival benefit in patients with glioblastoma who receive temozolomide‐based chemotherapy. A prospective randomized study may be indicated.